Immortalization of Human Keratinocytes Using the Catalytic Subunit of Telomerase - Beilin, A. K. (Dokl Biochem Biophys, 2021)
A new stable line of human keratinocytes was obtained. The cells have altered morphology, both abnormal chromosomal composition and expression of keratinocyte markers, do not show contact inhibition, could be cultured in various media and have limited stratification ability in vitro. Upon transplantation into nude mice the cells have tumorigenic properties.